Judicial Study Of Gender Transition (Transgender) On Integrity Distribution - KAMBA, Sri Nanang Meiske; SARSON, Moh. Taufiq Zulfikar; BAKUNG, Dolot Alhasni (Indonesia Strategic Sustainability, 2022)
Gender transition (transgender) is a current phenomena on a worldwide and national scale. The subject of transgender in Indonesia has numerous issues, one of which is the status of transgender in Indonesian law, particularly inheritance law, which is found in both the Civil Code and the Compilation of Islamic Law. The issue is that there is a legal vacuum surrounding transgender arrangements in inheritance distribution. According to the study's findings, the legal situation of transgender persons has not been explicitly defined, and there is a legal vacuum, resulting in an ambiguous distribution of inheritance for transgender people. In Islamic law, transgender inheritance is reverted to its original gender and does not take bodily changes into account. Meanwhile, under the Civil Code, inheritance is distributed based on the method of gaining inheritance.